'Both needed and threatened': Armed mothers in militant visuals. (February 2021) - Loken, Meredith
Because women are assumed to be nonviolent, their participation in militant groups can humanize organizations and legitimize rebellion. But gender beliefs are deeply engrained, and consequently women's involvement can also generate resistance. This article explores how militants navigate this tension through their political visuals, specifically analyzing images of 'armed mothers' across six diverse conflicts. Leveraging life-giving as the 'natural' role for women, these images signal violent disruption of everyday life and authorize political violence in response. But they also stress the temporariness of gender-role expansion, promising and preserving a 'return to normal'. Militant groups contextualize, justify, and humanize violent struggle through these images even in cases where women rarely participate on the front lines.